El reconocimiento de la huella digital e implementación de códigos electrónicos de verificación para garantizar la seguridad jurídica en la actividad notarial. - Salinas Quiñónez, Ammy Carmita (2022)
The present investigation deals with the study and analysis regarding the recognition of fingerprints in notarial headquarters since the recognition of fingerprints was being done by the secretaries of the Courts, by virtue of the attributions that they maintained according to the Organic Law of the Judicial Function, for that reason in This research demonstrates the need for fingerprint recognition to be clearly stipulated in the Notarial Law, in addition, the Organic Code of the Judicial Function does not contemplate the activities that the Court Clerks must carry out, in addition, there are no longer courts as such, but rather They are called Specialized Judicial Units and have secretaries, analysts and support staff, whose name is generally as servants of the Judicial Function and according to Art. 100 ibid. they must fulfill their duties as appropriate to the position they hold; ratifying it in numeral 2. Electronic verification codes are a novel concept within our environment, and their applicability in Law is scarce, their non-existent normative stipulation gives way to the lack of security in notarial activity. The research aims to elucidate precisely the practice of fingerprint recognition by notaries. A study methodology was proposed that encompassed various research methods and techniques that allowed demonstrating the importance of establishing the practice of fingerprint recognition and the use of electronic verification codes in notarial documents as notarial attribution. Finally, according to the analysis carried out, it is concluded that the practice of fingerprint recognition in the notarial office guarantees legal security in Ecuadorian legislation and the use of electronic verification codes in the notarial service allows 99.9% effectiveness in the security of documents. documents.